Lung Ultrasound in Hemodialysis Patients—Which Protocol Is More Accurate and Informative in Daily Clinical Practice: A Systematic Review - Christodoulos Keskinis; Konstantina Bacharidou; Stylianos Panagoutsos; Efstathios Mitsopoulos (Life)
Lung ultrasound can detect hidden lung congestion in hemodialysis (HD) patients, even though they present no symptoms of hypervolemia. The 28-zone protocol is the one mainly assessed in the majority of studies. However, it is quite time consuming, making its integration into daily clinical practice difficult. Alternative approaches have been proposed that require fewer scanning zones. This systematic review used various combinations of the following keywords: “Lung ultrasound”, “Hemodialysis”, “Scanning protocols”, “Scanning zones”, “28-points”, and “28-zones” via PubMed’s and Google Scholar’s search engines. Six relevant studies were obtained, five of which refer to the adult population and one to children. Initially, the first published study compared the 28-zone protocol to the 8-zone protocol, while three studies compared the 28-zone protocol to the 8-zone, 6-zone, and 4-zone protocols. Another study compared the 16-zone protocol to the 12-zone and 8-zone protocols. Finally, one study compared the 28-zone protocol to the 8-zone protocol in children. There are several alternatives in the literature for applying abbreviated versions of the 28-zone protocol to save time in daily clinical practice. However, none of these protocols provide the same accuracy as the 28-zone protocol. Therefore, it should be preferred when the clinical question regarding pulmonary congestion remains. Further multicenter studies are required to determine whether any shorter version of the 28-zone protocol can sufficiently replace it in daily clinical practice.